Dual-frequency anti-nonlinear sound-absorbing metasurface via multilayer nested microslit resonators. (7th March 2023) - Sun, Wei; Li, Li; Chu, Zhigang
Abstract: We propose a dual-frequency anti-nonlinear sound-absorbing metasurface (DASM) based on multilayer nested microslit resonators. Under the assumption of a linear system, the theoretical acoustic impedance of the DASM is derived by the transfer matrix method. Furthermore, the influence of structural parameters on sound absorption is also explored. The numerical and experimental results show that the proposed DASM can achieve quasi-perfect sound absorption at two low frequencies corresponding to the first two orders of the acoustic cavity mode frequencies of the structural unit, and enjoys strong anti-nonlinear performance and robustness to incident angles.